Remoção de nitrogênio de efluentes anaeróbios em reatores com atividade anammox - Josiane da Silva Fernandes (2019)
In the last decades with the population growth, the intensive use of fertilizers in agriculture and the release of effluents without treatment containing nitrogen have caused severe damages to water bodies. So, it becomes extremely important to do the treatment of domestic and industrial effluents, mainly for the removal of nutrients and organic matter. The anaerobic oxidation process of ammonia (Anammox) is very promising for the removal of nitrogen from effluents and is generally associated with other processes, such as partial nitrification (PN). Thus, continuous improvements for the effective application of the process in different types of effluent are still necessary. This study evaluated the performance of sequential batch reactors (SBR) with Anammox activity for: 1) nitrogen removal from anaerobically pretreated domestic effluent, 2) nitrogen removal from food waste digestate. The experiment was a two-step trial. Step 1, performed in SBR on a 2 L laboratory scale (SBR-Lab), and consisted of three experimental phases: 1) Enrichment of Anammox bacteria; 2) Feeding with domestic effluent plus nitrite; and 3) Evaluation of two intermittent aeration strategies (0.050 and 0.025L/min/Lreator) for the development of the PN/Anammox process for the removal of N-ammonia. Step 2 was a 500L pilot-scale SBR (Pilot SBR) two-phase trial: 1) Enrichment of Anammox bacteria; and 2) Operation with food residue digestate. The results for the laboratory SBR in Phase 1 were 41 and 91% efficiency of median removal of ammonia and nitrite, respectively. In Phase 2 the removal medians were 56% for ammonia and 98% for nitrite. In Phases 3 and 4 with the two aeration strategies evaluated, the values obtained were different from what is intended in the PN/Anammox process, since the ammonia consumed was oxidized to nitrate, therefore, the desired in these phases was not achieved (the removal of ammonia in this phase was 90% with total nitrite consumption and median nitrate production equal to 50mg/L). The results obtained in Phase 1 for the pilot SBR were median of ammonia removal efficiency of 31 and 32% of nitrite (with synthetic material); and in Phase 2, 67% of median ammonia removal and 99% of nitrite were obtained, showing greater Anammox activity in Phase 2, and indicating that it was possible to cultivate Anammox from real effluent (digestate of food waste) supplemented with nitrite. The detection results of the nitrogen cycle bacteria showed that the Anammox bacteria, ammonia oxidizers, nitrite oxidizers (Nitrospira and Nitrobacter) and denitrifiers were present in the reactors (laboratory and pilot SBR) in all tested phases; and therefore, they were involved in the removal and conversion of nitrogenous forms in both reactors.